Research on Effect of Powder Particle Size on Quality Performance of MIM Small Module Gears - Zhong Zhicheng; Pan Chunrong; Lin Ling; Ren Jihua (Jixie chuandong)
When using the process of metal powder injection molding (MIM) to prepare small module gears, in order to improve the quality and performance of the sintered parts of the gear, powder with different particle sizes is prepared. The sintering performance of the gear is analyzed by the melt flow meter, the porosity measurement software, the 2.5-dimensional image measuring instrument and the micro-Vickers hardness tester. The influence mechanism of particle sizes on the surface quality, porosity and shrinkage of gears is studied. The results show that due to the poor powder flow performance of the gear made of 5.0 μm powder, the powder concentration distribution is not uniform after sintering, there are black lines on the surface, and the dimensional shrinkage is not uniform, which affect the dimensional accuracy. Due to the poor sintering neck formation ability and slow diffusion process of the gear made of 9.0 μm powder, the porosity after sintering is high and the pore size is large. When the 7.0 μm powder is used to prepare the gear, the quality performance of the gear is the best. The gear has no surface defects, the porosity is reduced to 2.9%, the Vickers hardness value reaches 355, the shrinkage uniformity is high, the dimensional accuracy is high, and the accuracy of thetested items are better than class 7 according to the national standard GB 2363—1990.